Optimization Structure and Applications - Pearce, Charles.; Hunt, Emma. (Springer Optimization and Its Applications, 2009)
Optimization: Structure and Applications presents selected contributions from renowned researchers in the fields of operations research and industrial engineering. The text is divided into two parts: the first focuses on mathematical structure, and the second, on real-world applications. The book includes recent developments in several optimization-related topics such as decision theory, linear programming, turnpike theory, duality theory, convex analysis, and queueing theory. The applications presented include, but are not limited to, data imaging, network capacity allocation, water system management, and materials design. The 21 self-contained chapters in this volume are devoted to the examination of modern trends and open problems in the field of optimization. This book will be a valuable tool not only to specialists interested in the technical detail and various applications presented, but also to researchers interested in building upon the books theoretical results.